Cryo-correlative light and electron microscopy workflow for cryo-focused ion beam milled adherent cells - Klein, Steffen; Wachsmuth-Melm, Moritz; Winter, Sophie L.; Kolovou, Androniki; Chlanda, Petr (Correlative light and electron microscopy ; 4, 2021)
In situ cryo-electron tomography of cryo-focused ion beam (cryo-FIB) milled cells enables the study of cellular organelles in unperturbed conditions and close to the molecular resolution. However, due to the crowdedness of the cellular environment, the identification of individual macromolecular complexes either on organelles or inside the cytosol in cryo-electron tomograms is challenging. Cryo-correlative light and electron microscopy (cryo-CLEM) employs a fluorescently labeled feature of interest imaged by cryo-light microscopy that is correlated to cryo-electron microscopy maps of cryo-FIB milled lamellae using correlation markers discernable by both imaging methods. Here, we provide a protocol for a post-correlation on-lamella cryo-CLEM approach for localization of fluorescently labeled organelles of interest in cryo-lamellae after cryo-FIB milling and tomography of adherent plunge frozen cells.